SHA512 and MD5 Algorithm Vulnerability Testing Using Common Vulnerability Scoring System (CVSS) (Buana Information Technology and Computer Sciences (BIT and CS), 2022)
This paper discusses the comparison of the results of testing the OTP (One Time Password) algorithm on two encryptions, namely SHA512 and MD5 which are applied to the Reconciliation Application of the Dinas Pemberdayaan Masyarakat dan Desa Kabupaten Sukabumi. This study uses the Vulnerability Assessment and Penetration Testing (VAPT) method, which combines two forms of vulnerability testing to achieve a much more complete vulnerability analysis by performing different tasks in the same focus area. The vulnerability assessment uses the Common Vulnerability Scoring System (CVSS) method. The results showed that the Vulnerability Assessment and Penetration Testing (VAPT) method was proven to be able to identify the level of security vulnerability in the Reconciliation Application at the Dinas Pemberdayaan Masyarakat dan Desa Kabupaten Sukabumi with a vulnerability level score of 5.3 in the SHA512 environment with a medium rating and 7.5 in the MD5 environment. with high ratings. So, it can be concluded that the best algorithm for implementing OTP is SHA512